ANALYSIS OF FINANCIAL LITERACY AND FINANCIAL MANAGEMENT OF MSMEs IN THE CITY AND REGENCY OF TEGAL - Juli Riyanto Tri Wijaya; Eliada Herwiyanti (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in the economic development of the country. This is because MSMEs are the prime movers of national economic activity, are able to empower the community, provide jobs, and are able to maintain the balance of payments through export activities. The metal industry is a type of industry that supports the production of capital goods and supports other types of industry. The use of metal as the main raw material makes the metal industry have a major role in the growth and development of the national industry. This study uses primary data obtained by distributing questionnaires by random sampling to MSME actors engaged in the metal industry in Tegal. The research object consisted of all MSMEs in the City and Regency of Tegal and 38 research samples were obtained. The results of the study found that financial literacy has an influence on financial management in MSMEs engaged in metal in the City and Regency of Tegal. In addition, the level of financial literacy and financial management of MSMEs in the City and District of Tegal is quite good. The contribution of this research is as a reference for the government in assessing the level of financial literacy and financial management of MSMEs in the City and District of Tegal. This research is also useful for MSME actors to find out how important financial literacy and financial management are for the sustainability of their businesses.